A qualitative study of the psychological processes involved in the successful performances of Japanese athletes at international competitions held in Japan - Sasaki, J.; Fukui, K.; Suzuki, A.; Yonemaru, K.; Okuno, M.; Tachiya, Y. (Journal of High Performance Sport, 2019)
The purpose of this study was to qualitatively investigate the psychological processes that occur before and during the successful performances of Japanese athletes at international competitions held in Japan. Ten Japanese retired athletes (six female and four male) who had performed well in international competitions held in Japan participated a semi-structured interview. In the interview, the participants were asked to describe their experience in detail for approximately two hours. The taped and transcribed interviews were analyzed using the modified grounded theory approach (M-GTA: Kinoshita, 2003, 2007). The analysis yielded an integrated process model consisting following 18 concepts: (1) a larger audience than usual, (2) more media persons than usual, (3) feeling a pleasant tension, (4) controlling the media for their own convenience, (5) inconvenience caused by the restriction of activities, (6) assertive exploration for ways to feel refreshed, (7) experiencing a sense of responsibility, (8) peer pressure, (9) futile efforts, (10) unexpected situation, (11) being agitated, (12) perceived great urgency, (13) reflection, (14) turning defiant, (15) self-regulation, (16) concentrating on their own performance, (17) being motivated by the cheers from the Japanese audience, and (18) performing successfully. Furthermore, these concepts were arranged in chronological order, and they demonstrated two routes that led to a successful performance. The results suggested that flexible response to excitement of audience and media, overcoming pressure as a representative of the nation, and establishment of psychological skills necessary to be able to concentrate on one`s performance were important performance factors for athletes at international competitions held in the athlete`s home country.